Towards an integrated analytical framework of information and communications technology literacy: from intended to implemented and achieved dimensions - Lina Markauskaite (Information Research: An International Electronic Journal)
Introduction. Theoretical approaches and frameworks that help us to understand the contemporary notion of information and communication technology (ICT) literacy in the formal education sector are reviewed and examined. Method. The analysis is conducted from a technology (i.e., computer science) conceptual perspective. The focus is on those aspects of new literacies that are directly related to the use of ICT. Structured literature review and documentary research techniques are applied. Analysis. Relationships between ICT literacy, information literacy, media literacy and other new literacies are clarified. Important terms - 'ICT', 'literacy' and 'ICT literacy' - are discussed. An analytical framework for the investigation of contemporary understandings of ICT literacy is presented. Three analytical dimensions of ICT literacy - (1) intended, (2) implemented and (3) achieved - are employed in this framework. The main perspectives and structural approaches that can be applied for the examination of ICT literacy in each of these three dimensions are discussed. Results. The proposed analytical framework reveals links between (1) the conceptual approaches and initial aims of ICT literacy policies, proposed at the top-level of policymaking; (2) teaching and learning practices, implemented at the middle-level of educational system and (3) ICT literacy learning experiences and students' outcomes, expected at the base-level of educational system. Conclusion. . It is argued that this analytical framework can be applied for an integrated analysis of ICT literacy. The framework provides a conceptual structure for discovering inconsistencies in the understanding of ICT literacy at various levels of educational systems.